KONSTRUKSI LOGIKA KE-TUHANAN DALAM AL-QUR’AN PERSPEKTIF CHARLES S. PIERCE: KRITIK ATAS PAGANISME ARAB - Mahbub Ghozali (Aqidah-ta: Jurnal Ilmu Aqidah, 2021)
The Qur'an contains many verses relating to divine concepts. The explanation of divinity in the Qur'an is closely related to efforts to provide evidence of the truth of the Prophet's message and the truth of the concept of divinity in Islam. This problem is directly related to the divine concept of the Arab community as the object of conveying the al-Qur'an. The closeness of the concept of divinity to the concepts they understand makes the narrative of the verse have to enter and provide an effective rebuttal as possible. In this context, this study aims to find logical reasoning in every verse related to divinity, so that it makes it easy for Arabs to accept and believe in the concepts contained in Islam. To achieve these objectives, this study uses qualitative methods with the type of literature study research. To refine the data analysis process, this study uses the pragmatic philosophical approach of Charles S. Pierce. This research concludes that the narrative built by the Koran in arousing the divine awareness of the Arab community is logically carried out and fully accepted. The narrative is aimed at exposing their belief in the definition of God by doubting existing beliefs. With this doubt, everyone who realizes that a concept that has been believed to be wrong will conduct direct research and observation of the truth of the concept of divinity in Islam. Identification of icons, indexes, symbols correctly to the essence of God led them to an attitude of acceptance of Islam and all forms of divine concepts in it.